Photodissociative Cross-Linking of Non-covalent Peptide-Peptide Ion Complexes in the Gas Phase - Nguyen, Huong T H; Andrikopoulos, Prokopis C; Rulíšek, Lubomír; Shaffer, Christopher J; Tureček, František (Journal of the American Society for Mass Spectrometry, 2018)
We report a gas-phase UV photodissociation study investigating non-covalent interactions between neutral hydrophobic pentapeptides and peptide ions incorporating a diazirine-tagged photoleucine residue. Phenylalanine (Phe) and proline (Pro) were chosen as the conformation-affecting residues that were incorporated into a small library of neutral pentapeptides. Gas-phase ion-molecule complexes of these peptides with photo-labeled pentapeptides were subjected to photodissociation. Selective photocleavage of the diazirine ring at 355 nm formed short-lived carbene intermediates that underwent cross-linking by insertion into H-X bonds of the target peptide. The cross-link positions were established from collision-induced dissociation tandem mass spectra (CID-MS3) providing sequence information on the covalent adducts. Effects of the amino acid residue (Pro or Phe) and its position in the target peptide sequence were evaluated. For proline-containing peptides, interactions resulting in covalent cross-links in these complexes became more prominent as proline was moved towards the C-terminus of the target peptide sequence. The photocross-linking yields of phenylalanine-containing peptides depended on the position of both phenylalanine and photoleucine. Density functional theory calculations were used to assign structures of low-energy conformers of the (GLPMG + GLL*LK + H)+ complex. Born-Oppenheimer molecular dynamics trajectory calculations were used to capture the thermal motion in the complexes within 100 ps and determine close contacts between the incipient carbene and the H-X bonds in the target peptide. This provided atomic-level resolution of potential cross-links that aided spectra interpretation and was in agreement with experimental data. Graphical Abstract ᅟ.
Keywords: Born-Oppenheimer molecular dynamics; Diazirine tags; Peptide-peptide complexes; Cross-linking; Photodissociation